Ethical attitudes of accounting and business students : Malaysian evidence - Yahaya Rusliza, Zainol Zuraidah, Ahamad Rapani Norhanani, Mat Norwani Norlia, Samsudin Norsamsinar, Mat Jizat Jessnor Elmy (Universiti Pendidikan Sultan Idris, 2016)
Ethical attitudes of accounting and business students : Malaysian evidence by Yahaya Rusliza, Zainol Zuraidah, Ahamad Rapani Norhanani, Mat Norwani Norlia, Samsudin Norsamsinar, Mat Jizat Jessnor Elmy,